NEOLOGISMS AND WORD FORMATION PROBLEMS - Xamzaev Sobir Amirovich; Atadjanova Maftuna Shuxratovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
The attention of linguists is mainly attracted by neologisms related to scientific and technical topics, due to the rapid progress of science and technology in recent decades. This fact had a great impact on the information sphere. It is in the media that all global events occurring in the world are reflected. At the moment, our society is characterized as “informational”, and, therefore, it is based on the processes of collecting, storing and transmitting information, which provides an opportunity for its implementation and further development.